HOW DOES FINANCIAL LITERACY IMPACT ACCESS TO BANKING PRODUCTS AND SERVICES? (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of financial literacy on the utilization of banking products and services in the Kalaburagi District of Karnataka. Using primary data collected from 432 households across 36 villages, the research examines how varying levels of financial literacy influence awareness and operational engagement with 14 banking products. The empirical evidence shows significant disparities in financial literacy, with nearly half of the population exhibiting low financial literacy. Which correlates with limited usage of more complex financial products. Regression analysis demonstrates that financial literacy significantly predicts the utilization of banking products, explaining 28 per cent of the variance. The study shows the role of financial literacy in enhancing financial inclusion and advocates for targeted financial education programs to improve financial behaviors and engagement with banking services. The results establish the importance of both supply-side and demand-side strategies in achieving comprehensive financial inclusion, with financial literacy emerging as a key enabler of effective financial decision-making and economic growth.